Advances in prostate cancer research models: From transgenic mice to tumor xenografting models - Yuejiao Huang; Chun Cheng; Chong Zhang; Yonghui Zhang; Miaomiao Chen; Douglas W. Strand; Ming Jiang (Asian Journal of Urology)
The identification of the origin and molecular characteristics of prostate cancer (PCa) has crucial implications for personalized treatment. The development of effective treatments for PCa has been limited; however, the recent establishment of several transgenic mouse lines and/or xenografting models is better reflecting the disease in vivo. With appropriate models, valuable tools for elucidating the functions of specific genes have gone deep into prostate development and carcinogenesis. In the present review, we summarize a number of important PCa research models established in our laboratories (PSA-Cre-ERT2/PTEN transgenic mouse models, AP-OX model, tissue recombination-xenografting models and PDX models), which represent advances of translational models from transgenic mouse lines to human tumor xenografting. Better understanding of the developments of these models will offer new insights into tumor progression and may help explain the functional significance of genetic variations in PCa. Additionally, this understanding could lead to new modes for curing PCa based on their particular biological phenotypes. Keywords: Prostate cancer, Transgenic mouse lines, Tumor xenografting models, Translational medical systems